International Relations and Foreign Policy in the Middle East: PLO, Hizbullah, and KRG as Statelike Actors - Aqra, Zakia (Πανεπιστήμιο Πελοποννήσου, 2022)
This thesis examines the foreign policy of statelike actors; that are entities that blur the line between state and armed non-state actors. It employs neoclassical realism, which hereto has been firmly state-centric, arguing that the approach and methodology of neoclassical realism has the explanatory power to better understand statelike actors’ foreign policy on a regional level. The thesis explores the foreign policy of three different yet similar actors; a national liberation movement, the Palestine Liberation Organisation (PLO); an Islamist political party and an Islamic social movement, Hizbullah; and a secessionist movement, the Kurdistan Regional Government (KRG). Despite their diverse nature and aspirations, these three actors display a high level of stateness, including the ability to conduct foreign policy, without possessing international legal recognition. Drawing from neoclassical realism, the thesis identifies specific intervening variables – the leadership’s perception of the system, its strategic culture, the state-society relations and institutions–while introducing an additional variable; the notion of territoriality. In turn, the thesis explores, first, how these intervening variables interact and engage with the structural system and stimuli (independent variable) in producing foreign policy choices (Type II) and, second, whether the statelike actors’ foreign policy produces structural outcomes (Type III). The thesis demonstrates that in all foreign policy choices the leadership’s perception, strategic culture and territoriality play an equally important and decisive role in the statelike actors’ foreign policy choices. Conversely, foreign policy institutions have no impact. Moreover, given the monocracy of these actors, state-society relations have a medium-level impact, except when their relations are on the verge of collapse, which delegitimises the leadership, rending the state-society relations a decisive variable. Finally, the thesis shows that statelike actors’ foreign policy impacts regional dynamics but does not produce structural outcomes per se.
Διεθνείς Σχέσεις και Εξωτερική Πολιτική στη Μέση Ανατολή: η Οργάνωση για την Απελευθέρωση της Παλαιστίνης, η Χεζμπολλάχ και η Περιφερειακή Κυβέρνηση του Κουρδιστάν ως Δρώντες με Οιονεί Κρατική Υπόσταση
Keywords: Middle East; International relations; Middle East--Foreign relations; Palestine Liberation Organisation (PLO); Hizbullah; Kurdistan Regional Government (KRG); foreign policy; neoclassical realism; statelike actors; armed non-state actors; Οργάνωση για την Απελευθέρωση της Παλαιστίνης (ΟΑΠ); Περιφερειακή Κυβέρνηση του Κουρδιστάν; Χεζμπολλάχ; εξωτερική πολιτική; νεοκλασικός ρεαλισμός; δρώντες με οιονεί κρατική υπόσταση; ένοπλοι μη-κρατικοί δρώντες